The Estradiol Synthesis Inhibitor Formestane Diminishes the Ability of Sevoflurane to Induce Neurodevelopmental Abnormalities in Male Rats - Wang, Jie; Yang, Baofeng; Ju, Lingsha; Yang, Jiaojiao; Allen, Andrea; Zhang, Jiaqiang; Martynyuk, Anatoly E. (Frontiers in Systems Neuroscience, 2020)
Background In rodents, the period of increased vulnerability to the developmental effects of general anesthetics coincides with the period of age-specific organizing (masculinizing) effects of the major female sex hormone 17β-estradiol (E2) in the male brain and excitatory GABA type A receptor (GABAAR) signaling. We studied whether E2 synthesis and excitatory GABAAR signaling are involved in the mediation of the developmental effects of sevoflurane in male rats. Methods Male Sprague-Dawley rats were pretreated with the inhibitors of E2 synthesis, formestane, or the Na+-K+-2Cl– (NKCC1) Cl– importer, bumetanide, prior to sevoflurane exposure for 6 h on postnatal (P) day 4, P5, or P6. We tested whether a subsequent exposure of these rats to sevoflurane on P∼10 would cause electroencephalography (EEG)-detectable seizures. We also evaluated their behavior during the elevated plus maze (EPM) test on P∼60, prepulse inhibition (PPI) of acoustic startle responses on P∼70, and corticosterone secretion to physical restraint on P∼80. Results The rats neonatally exposed to sevoflurane responded to repeated exposure to sevoflurane with increased EEG-detectable seizures (F(3,24) = 7.445, P = 0.001) and exhibited deficiencies during the EPM (F(3,55) = 4.397, P = 0.008) and PPI (F(3,110) = 5.222, P = 0.003) tests. They also responded to physical restraint with heightened secretion of corticosterone (F(3,16) = 11.906, P < 0.001). These parameters in the sevoflurane-exposed rats that were pretreated with formestane or bumetanide were not different from those in the control rats. Conclusion These results, along with previously published data, suggest that sevoflurane-enhanced E2 synthesis and excitatory GABAAR signaling at the time of sevoflurane anesthesia are involved in the mediation of the neurodevelopmental effects of the anesthetic in male rats.